Doop as die deur tot die nagmaal: "n Perspektief op kinderdeelname aan die nagmaal - Otto, J. (Hervormde teologiese studies, 2000)
Baptism as the gateway to the Eucharist: a perspective onchild participation in the Eucharist. This article invesigates the relationship between Baptism and the Eucharist andargues that baptism forms the gateway to meaningfully participating in the Eucharist. Children are excluded from participation in the Eucharist because the act of being baptised passes children's comprehension. It is argued that the baptism of a person has to be appropriated for the person to be able to meaningfully participate in the Lord's supper. Confession of faith in public is such an act of appropriation.